A randomized clinical trial on the efficacy of a patient-adapted autonomous exercise regime for patients with head and neck cancer. Issue 3 (March 2020) - Steegmann, Julius; Bartella, Alexander K.; Kloss-Brandstätter, Anita; Kamal, Mohammad; Hölzle, Frank; Lethaus, Bernd
Abstract: Patients undergoing surgical therapy of head and neck malignancies are known to exhibit a high number of comorbidities and frequently present a high nosocomial morbidity. Physiotherapy (PT) improves the clinical course of patients after extensive surgery. The aim of this study was to establish and then compare an additional individualized autonomous exercise plan with standard physiotherapy. 69 consecutive patients undergoing surgical treatment of head and neck cancer were randomized into two groups. The control group received standard clinical physiotherapy, the intervention group an additional autonomous exercise plan, adapted to the patient's performance profile. The patients randomized to the intervention group showed significantly fewer signs of fatigue (5.5 ± 3.5 vs. 3.7 ± 2.7, p = 0.048) and fewer digestive problems (4.7 ± 3.3 vs. 2.3 ± 2.7; p = 0.009) compared with the patients of the control group. In addition, a significantly shorter hospital stay was observed (17.7 ± 6.3 vs. 13.4 ± 3.4 days, p = 0.005), which was positively influenced by the early start of the exercises (r = 0.623, p = 0.001) and frequent practice (r = 0.432, p = 0.031). Patients with head and neck cancer therapy can benefit from an autonomous, individualized exercise plan. In coordination with the physiotherapists, mobilization should be as early and intensive as possible.